Integrating Traditional Medicine into Mainstream Healthcare Systems: Challenges and Opportunities - Dini Aulia Cahya; Riskha Dora Candra Dewi; Aninda Tanggono; Rachmad Hidayat (Riwayat: Educational Journal of History and Humanities, 2025)
The integration of traditional medicine into mainstream healthcare systems presents both significant challenges and unique opportunities. This study employs a literature review methodology to examine the current landscape of traditional medicine practices and their potential role within conventional healthcare frameworks. By analyzing various studies, policy documents, and case reports, this paper identifies key barriers to integration, including regulatory issues, lack of standardization, and the prevailing skepticism among healthcare professionals. Additionally, it highlights the opportunities for enhanced patient care through a more holistic approach that combines the strengths of both traditional and modern medical practices. The findings suggest that successful integration requires collaborative efforts among stakeholders, including policymakers, healthcare providers, and traditional medicine practitioners. Furthermore, the study emphasizes the need for comprehensive training programs to educate healthcare professionals about traditional medicine and its benefits, as well as the establishment of regulatory frameworks to ensure safety and efficacy. This paper contributes to the growing discourse on healthcare integration by providing insights into the complexities of merging traditional and modern medical systems and offering recommendations for future research and policy development.